Understanding engineering mathematics / Bill Cox. - Cox, Bill, 1945- (Newnes, 2001)
Bill Cox's core undergraduate textbook on engineering mathematics is designed to enable students to diagnose their strengths and weaknesses and focus their efforts where needed. The text is linked to a website that offers further guidance.